A Review of Triple Negtive Marker of IHC in Medullary Carcinoma Breast: An Uncommon Substype with Good Prognosis - Sahay, Swati; Bansal, Aarushi; Singh, Aditya (Annals of Pathology and Laboratory Medicine, 2019)
Medullary carcinoma of the breast is an uncommon variant of invasive ductal carcinoma, which constitutes nearly 5% of all breast cancers in men and women. These tumours are often associated with favourable prognosis despite showing aggressive behaviour. In this study a patient presented with history of breast lump aged 48 years in left breast since one year .In mammography it was described as BIRADS II and fine needle aspiration cytology showed suspicious for malignancy .Histopathology report showed medullary carcinoma breast lesion. Immunochemistry was also done for ER , PR and Her-2neu and it showed negative for ER ,PR and HER 2 Neu.